Clear Cell Tumor With Melanocytic Differentiation and ACTIN-MITF Translocation: Report of 7 Cases of a Novel Entity. (July 2021) - de la Fouchardiere, Arnaud; Pissaloux, Daniel; Tirode, Franck; Karanian, Marie; Fletcher, Christopher D.M.; Hanna, John
Abstract : Clear cell morphology is an uncommon finding in tumors. A subset of clear cell neoplasms also shows melanocytic differentiation, including clear cell sarcoma, PEComa, and some subtypes of renal cell carcinoma. A hallmark of these tumor types is the activation of a member of the MIT/TFE family of transcription factors, which includes MITF, TFE3, TFEB, and TFEC. Microphthalmia transcription factor (MITF is the master regulator of melanin synthesis, while TFEB plays a critical role in lysosome biogenesis. Cytogenetic translocations involving TFE3 and TFEB are now well described in multiple tumor types, but there has been little evidence to suggest similar regulation of MITF. Here we describe a series of 7 clear cell cutaneous neoplasms with melanocytic differentiation that are characterized by ACTIN-MITF gene fusions, either ACTB-MITF or ACTG1-MITF . The chromosomal breakpoints preserve MITF's dimerization and transcriptional activation domains, suggesting that these fusion proteins likely result in hyperactive MITF function, analogously to the previously reported TFE3 and TFEB fusions. Our findings indicate that MITF gene rearrangements may be key drivers of tumor pathogenesis and expand the spectrum of neoplasia associated with the MIT/TFE family.